Knowledge on HIV/AIDS and Sexual Behaviours among Long-distance Truck Drivers at Kazungula Weigh Bridge Terminal, Chobe District, Botswana (African Journal of Biomedical Research, 2023)
Long-distance truck drivers (LDTDs) have a higher rate of HIV infection than the general population. This is attributed to their high mobility and their being out of their homes for protracted periods. LDTDs stop for a day or more at Kazungula weigh bridge terminal, making it a lucrative rendezvous for commercial sex work. Risky sexual behaviour predisposes LDTDs to contracting and spreading HIV. The aim of this study is to determine the level of knowledge of HIV/AIDS and the sexual behaviour of the LDTDs at Kazungula weigh bridge terminal. Quantitative, cross-sectional-descriptive methods were employed to study the LDTDs at Kazungula weigh bridge terminal in the Chobe District. A simple random sampling technique was used to produce a sample of 399 truck drivers who consented to participate in the study. A questionnaire (written in English and translated into Setswana) was used to collect socio- demographic data and establish the knowledge of HIV/AIDS and sexual behaviours of LDTDs. A total of 399 LDTDs participated in this study. The level of knowledge about HIV/AIDS was high among the LDTDs, but regardless of this, LDTDs engaged in sexually risky behaviours. All participants (100%) had heard about HIV/AIDS and the common sources of information were the media (65.9%) and school (62.9%). Most of the LDTDs (96.99%) knew that AIDS is caused by HIV, and the level of education was not a predictor of the level of knowledge of HIV/AIDS among the LDTDs, with a correlation of 0.597 (not significant). About 12.03% believed that HIV/AIDS is caused by witchcraft and 23.31% did not agree that HIV/AIDS has no cure. This has an association with the level of education (P